BENIGN CEPHALIC HISTIOCYTOSIS - Pereira, Neide; Brinca, Ana; Tellechea, Óscar; Cordeiro, Margarida Robalo (Journal of the Portuguese Society of Dermatology and Venereology, 2013)
Benign cephalic histiocytosis is a type of non-Langerhans histiocytitic disorder. Of unknown etiology, is a self-healing disease, arising in childhood and is characterized by papular lesions primarily affecting the face. We describe a 10-month-old girl who presented with 6 months of evolution, yellow-red papules asymptomatic, on her face. The histological and immunohistochemical study showed the presence of a diffuse infiltration of histiocytes, throu- ghout the dermis, negative for the protein S100 and CD1a and positive for CD68. Given the diagnosis of benign cepha- lic histiocytosis, we chose an expectant attitude verifying complete regression after one year of follow-up. Since its description by Gianotti, et al. in 1971, only 40 cases were reported in the literature. KEYWORDS – Histiocytosis; Non-Langerhans-cell; Facial dermatoses; Skin diseases.